Improving Vaccine Product Quality Using the Six Sigma DMAIC Method: A Case Study at PT Vaksindo Animal Nusantara - Supriyono; Bayu Nur Kuncoro; I Gede Novian Suteja; Junaenah; Wahyu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Vaccindo is the first and most trusted local vaccine producer to meet the vaccine needs of farmers in Indonesia. This study was to determine the quality of IBH who is still in the trial phase, vaccine production at PT. Vaksindo and to determine the application of defect control with Six Sigma method on defective vaccine products. to obtain the concentration of the virus produced on average does not enter the minimum threshold of the standard set, that is 7.0 TCID50 /0.1 mL in trial phase, Defect Per Million Opportunity (DPMO) is 826408.73, which means that in every million times of product produced in each production has a defective product of 826408.73, if it is converted into a sigma table the DPMO value does not even enter the first sigma level is the value of 690,000 DPMO, which means the process carried out in the IBH vaccine production process by PT. Vaksindo coverage is still below 30.9% to improve this, improvements are such as testing the level of viruses of VCT titration in each sample post harvest and pre production to maintain the quality of the antigen produced, as well as propagation seed is done at the maximum limit that can be obtained so that when propagated to antigen, the titer value or concentration of the virus does not go down and remaining standard.